2014
DOI: 10.1037/a0036004
|View full text |Cite
|
Sign up to set email alerts
|

Mothers, fathers, sons and daughters: Parental sensitivity in families with two children.

Abstract: Most studies on early childhood parenting include only mothers. Fathers are rarely observed in interaction with their young children, although they play an important role in the socialization of their children. In this study, we observed parenting of mothers and fathers toward their sons and daughters in families with two children, using a within-family approach in a sample with systematically varying family constellations. Participants included 389 families with two children (1 and 3 years of age). Parenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 54 publications
6
86
1
2
Order By: Relevance
“…In consequence, the uncertain state of this literature likely reflects these scientific and methodological disparities (Michalski & Shackelford, 2001; Price & Hare, 1969). For mean level analyses, depending on these parameters, mothers have been reported to favor firstborns (e.g., Belsky, Gilstrap, & Rovine, 1984; Dunn & Plomin, 1986; Hallers-Haalboom et al, 2014; Jacobs & Moss, 1976; van IJzendoorn et al, 2000) or favor secondborns (e.g., Moore, Cohn, & Campbell, 1997; Ward, Vaughn, & Robb, 1988) or treat first- and secondborns equitably (e.g., Dunn & Plomin, 1986; Dunn, Plomin, & Nettles, 1985; Holden & Miller, 1999). By contrast, mothers’ socioemotional interactions with their two children tend to show moderate order consistency (e.g., Dunn & Plomin, 1986; Dunn, Plomin, & Daniels, 1986; Dunn et al, 1985; Robinson & Little, 1994; van IJzendoorn et al, 2000), albeit with some exceptions dictated by moderator.…”
Section: Emotional Interactions In Mothers Firstborns and Secondbormentioning
confidence: 99%
“…In consequence, the uncertain state of this literature likely reflects these scientific and methodological disparities (Michalski & Shackelford, 2001; Price & Hare, 1969). For mean level analyses, depending on these parameters, mothers have been reported to favor firstborns (e.g., Belsky, Gilstrap, & Rovine, 1984; Dunn & Plomin, 1986; Hallers-Haalboom et al, 2014; Jacobs & Moss, 1976; van IJzendoorn et al, 2000) or favor secondborns (e.g., Moore, Cohn, & Campbell, 1997; Ward, Vaughn, & Robb, 1988) or treat first- and secondborns equitably (e.g., Dunn & Plomin, 1986; Dunn, Plomin, & Nettles, 1985; Holden & Miller, 1999). By contrast, mothers’ socioemotional interactions with their two children tend to show moderate order consistency (e.g., Dunn & Plomin, 1986; Dunn, Plomin, & Daniels, 1986; Dunn et al, 1985; Robinson & Little, 1994; van IJzendoorn et al, 2000), albeit with some exceptions dictated by moderator.…”
Section: Emotional Interactions In Mothers Firstborns and Secondbormentioning
confidence: 99%
“…There are significant differences between the quantity and quality of mothers' and fathers' involvement with the child (Parke, 2002 for a review). Differences in the amount of time mothers and fathers spend with the child, the type of joint activities they perform and their style of interaction, have been PRESCHOOL CHILDREN'S PROSOCIAL BEHAVIOR 5 reported (Hallers-Haalboom et al, 2014;Lewis & Lamb, 2003;McBride & Mills, 1993;Roopnarine, Fouts, Lamb, & Lewis-Elligan, 2005;Yeung, Sandberg, Davis-Kean, & Hofferth, 2001). Although both parents can be equally sensitive and responsive, mothers tend to be verbal and didactic in their play, while fathers tend to engage in a more physically stimulating and unpredictable play (Lewis & Lamb, 2003;Parke, 2002).…”
Section: Changing Roles: Mother and Fathermentioning
confidence: 99%
“…It is possible that the difference in the pathways was due to the fact that at each age from 38 to 80 months (although no longer at age 10), MRO in mother-child dyads was significantly higher than MRO in father-child dyads (a finding consistent with Hallers-Haalboom et al, 2014). This was also true for children’s security measure at age 8.…”
Section: Discussionmentioning
confidence: 86%
“…For example, compared to infants’ interactions with mothers, which comprised more caregiving, those with fathers have been described as comprising a higher proportion of play (Lamb, 1977). In a recent study, mothers were more sensitive during free play with their young (1- and 3-year-old) children than fathers (Hallers-Haalboom et al, 2014). Despite the possible differences, however, a recent meta-analysis indicated that fathers’ sensitivity predicts children’s security, much as it does for mothers (Lucassen et al, 2011).…”
Section: The Examination Of Mother-child and Father-child Relationshipsmentioning
confidence: 92%
See 1 more Smart Citation